Обработка измерительной информации в микромеханических гироскопах; Вестник науки Сибири; № 2 (8) - Баранов П. Ф. Павел Федорович; Бориков В. Н. Валерий Николаевич; Нестеренко Т. Г. Тамара Георгиевна; Цимбалист Э. И. Эдвард Ильич (Инженерные науки, 2013)
Заглавие с титульного листа